Lipohypertrophy contributing to severe diabetic ketoacidosis in type 1 diabetes: An increasing problem in the context of the COVID‐19 pandemic?. Issue 11 (19th November 2022) - Smith, Emilia Imogen; Ciutac, Andra; Smith, Jamie C.
Abstract: A 57‐year‐old man with type 1 diabetes was admitted with diabetic ketoacidosis during the COVID‐19 pandemic. On examination, there was evidence of severe lipohypertrophy on his abdomen. Repeated injection of subcutaneous insulin into areas of lipohypertrophy was thought to have contributed to the development of ketoacidosis. Abstract : Lipohypertrophy is a complication of insulin injection therapy, leading to erratic systemic absorption of insulin and contributing to the development of diabetic ketoacidosis. Injection sites need to be examined carefully at diabetes annual reviews.